تأثير استخدام وسيلة باور بوينت(Power Point) على اهتمام الطلاب بتعلم مهارة الكلام في المدرسة المتوسطة الإسلامية الحكومية 10 بادنج باريامان - Putri, Sukma Ayni; Dewi, Yelfi; Anas, Al Baihaqi; Rizal, Eka (Lembaga Yasin AlSys, 2023)
The problem of this researchshe Students' interest in learning speaking skill declines because the Arabic language teacher uses traditional means such as the blackboard Although there are many innovative teaching aids nowadays, such as using computer technology, there are many applications that can be used as teaching aids, one of which is Power Point. This causes students to lack understanding and lower their results in learning speaking skill. In this research, the researcher used an experimental design pre experimental kind of one group pretest posttest. The research population is the eighth grade students, and their number is 60 people, and the research sample is the eighth grade students (2), and their number is 30 people. Sample selection method purposive sampling. The research tools used in this research are the questionnaire and the documentation to analyze the data, The researcher used a test paired t-test. Search results is the value of the pre-test and the value of the post-test were explained with significance (sig-2 tailed) p= 0,000 smaller than 0,05. So there is positive effect of using the Power Point method on students' interest in learning speaking skill in Government Islamic Middle School 10 Padang Pariaman.